New starches for the food industry: Curcuma longa and Curcuma zedoaria - Leonel, M.; Sarmento, SBS; Cereda, M. P. (Elsevier B.V., 2003)
The evolution of the food sector has increased interest in the identification of new starches with distinct properties. Curcuma longa and Curcuma zedoaria rhizomes, which are already used in industry to obtain food coloring and pharmaceutical products, may become commercially interesting as starch raw materials. This work aimed to characterize the starch of two Curcuma species. The results revealed that the rhizomes of two species showed low dry matter and high starch contents. The amylose contents of the starches (22% C. longa and 21% C. zedoaria) were similar to potato starch. The results of microscopic analysis showed flat triangular shape and the size was 20-30 mum for two starches. The final viscosity of C longa was high (740 RVU) and the pasting temperature was 81 degreesC. In C. zedoaria the final viscosity was 427 RVU and the pasting temperature was 78 degreesC. These results differed from standard commercially used natural starches. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: starch; viscosity; microscopy